2016
DOI: 10.1016/j.jhealeco.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

An elicitation of utility for quality of life under prospect theory

Abstract: This paper performs several tests of decision analysis applied to the health domain. First, we conduct a test of the normative expected utility theory. Second, we investigate the possibility to elicit the more general prospect theory. We observe risk aversion for gains and losses and violations of expected utility. These results imply that mechanisms governing decisions in the health domain are similar to those in the monetary domain. However, we also report one important deviation: utility is universally conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 52 publications
8
30
0
Order By: Relevance
“…Previous research on individual decision making under risk already reported loss aversion to be expandable from the monetary to the health field (Attema et al, 2013;Attema et al, 2014). Moreover, Polman (2012) found evidence for loss aversion using monetary outcomes when people have to decide on behalf of others, although to a smaller extent than when deciding for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on individual decision making under risk already reported loss aversion to be expandable from the monetary to the health field (Attema et al, 2013;Attema et al, 2014). Moreover, Polman (2012) found evidence for loss aversion using monetary outcomes when people have to decide on behalf of others, although to a smaller extent than when deciding for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…McNeil et al 1982), and although there has been some limited testing over midrange probabilities of twofold reflection-e.g. Attema et al (2013Attema et al ( , 2016 observed risk aversion over both gains and losses for life years-there has not been any direct testing of the fourfold reflection effect at all.…”
Section: Evidence Of the Reflection Effectmentioning
confidence: 99%
“…of reduced quality of life (end of life context), as it has been observed that preferences for health problems involving quality of life can differ from preferences in situations where outcomes are defined in terms of duration (Attema, Brouwer, & l'Haridon, 2013;Attema, Brouwer, l'Haridon, & Pinto-Prades, 2016). Notice that the outcomes H1 to H4 took the same values in each of the three health contexts.…”
Section: The Health Contextsmentioning
confidence: 99%